Study of Arabian Seawater Temperature Fluctuations - M. Arif Hussain; Shaheen Abbas; M. Rashid Kamal Ansari; Asma Zaffar (Journal of Basic & Applied Sciences, 2012)
It is well known that the ocean has an important role in climate variability and change. To study the variations in sea-surface temperature (SST) of Arabian sea near Karachi coastal region, we apply the probability distributions theory as it gives more insights of SST fluctuating behavior. In this regard the adequacy of Normal. Gamma, and Lognormal probability distributions is tested with the help of Kolmogorov-Smirnov D-test. It is found that most of the months of the year follow Normal probability distribution, whereas April, August, October, and November follow Lognormal probability distribution. Further, using the distribution parameters mean and standard deviations of monthly SST are also calculated, which come out to be (23.33 ± 0.316), (23.19 ± 0.300), (24.36 ± 0.312), (26.27 ± 0.360), (28.31 ± 0.325), (29.19 ± 0.347), (28.64 ± 0.346), (27.38 ± 0.364), (27.34 ± 0.322), (27.61 ± 0.311), (26.43 ± 0.352), (24.65 ±0.380).